Time and dose of irrigation impact Tuber melanosporum ectomycorrhiza proliferation and growth of Quercus ilex seedling hosts in young black truffle orchards - Olivera, Antoni; Antonio Bonet, Jose; Oliach, Daniel; Colinas, Carlos (MYCORRHIZA, 2014)
In Mediterranean climate, young truffle-oak orchards are subjected to drought episodes that can compromise the development of Tuber melanosporum. We investigated the responses of T. melanosporum to water supply in three periods: May to July, August to October, and May to October. In each period, five water doses were established: 0, 25, 50, 75, and 100 % of the reference evapotranspiration (ETo). Five orchards were planted with Quercus ilex inoculated with T. melanosporum, and in each orchard, we arranged a two-factorial design with irrigation period and irrigation dose as main factors to test their combined effects on the development of both T. melanosporum and Q. ilex after 3 years in the field. Irrigation period significantly interacted with irrigation doses for the absolute presence per seedling of T. melanosporum mycorrhizae. Irrigation in May-July increased significantly T. melanosporum colonization in seedlings irrigated with 50 % ETo dose compared to the 0 % ETo dose. A similar pattern with smaller differences in means was observed in August-October period, but the irrigation doses did not change T. melanosporum colonization when we watered from May to October. We found ectomycorrhizae different from T. melanosporum in 51 % of the seedlings studied, but their presence was marginal. Our results suggest that a moderate irrigation dose promotes seedling growth and number of fine root tips per unit of fine root length, which may be potentially colonized by T. melanosporum.
Keywords: Black truffle; Ectomycorrhizae; Evapotranspiration; Preproduction; Quercus ilex

Weed control modifies Tuber melanosporum mycelial expansion in young oak plantations - Olivera, Antoni; Antonio Bonet, Jose; Palacio, Lorena; Liu, Bing; Colinas, Carlos (ANNALS OF FOREST SCIENCE, 2014)
Black truffle (Tuber melanosporum) cultivation is a promising agro-forestry alternative for Mediterranean rural areas, but adequate weed control at seedling establishment still remains a challenge in black truffle plantations. The aim of this study is to evaluate the effects of several weed control strategies on early development of Quercus ilex seedlings and the symbiotic T. melanosporum. In a young black truffle-inoculated holm oak plantation, we assessed for 3 years the effects of two types of mechanical weed control and five mulches in a young Q. ilex plantation inoculated with T. melanosporum. Herbaceous cover, seedling growth and abundance of T. melanosporum mycelium, based on PCR analysis of soil DNA extracts using T. melanosporum-specific primers, were estimated to determine the effectiveness of these treatments in controlling weeds and supporting the growth of both the host tree and the target fungus. The amount of T. melanosporum mycelium in the soil 30 cm around the seedlings was larger under double-layer white mulch than in the rest of treatments tested. Under the white colour mulches, which had the largest light reflection, we registered the cooler soil temperature, and the best weed control was observed on the single- and double-layer black truffles and double-layer white mulch. The effects of double-layer white mulch on herbaceous cover, soil temperature, reflected light, and the expansion of T. melanosporum bring us closer to being able to substitute traditional tilling of truffle orchards for the less expensive mulching treatments.
Keywords: Mulch; Quercus ilex; Soil mycelium; Tubermelanosporum; Weed control